IMPLEMENTASI PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) PILAR PERTAMA DI DESA BOLA - Oliva Nurhayati Nirma; Anita Lado (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
In Bola Village, Bola District, Sikka Regency implemented a government program related to STBM (community-based total sanitation) with the following pillar indicators: stop open defecation (BABS), wash hands with soap, clean water treatment, waste treatment, liquid waste treatment . This study aims to determine the impact of the STBM program, especially for the first pillar of stopping open defecation in Bola Village. This research uses a qualitative method with the triggering method. the discussion of this research shows that the implementation of the first pillar STBM program has been carried out properly and smoothly in accordance with the planned stages. All facilitators from both the health office and the village government have monitored and evaluated with verification the implementation of the program to procure healthy latrines for the community.